Update on the Epigenomic Implication of Embryo Cryopreservation Methods Applied in Assisted Reproductive Technologies With Potential Long-Term Health Effects - Reyes Palomares, Arturo; Rodriguez-Wallberg, Kenny A. (Frontiers in Cell and Developmental Biology, 2022)
Cryopreservation of embryos has become an efficient method in Assisted Reproductive Technologies (ART) and these methods are currently performed at nearly all fertility centers around the globe. The methods for cryopreservation have also proven to optimize pregnancy rates and as a consequence, an increasing number of children are being born through these techniques worldwide. However, long-term follow-up studies of children born through ART are scarce, and concerns about the long-term health effects on individuals conceived through ART have been raised. The relevant genomic transformations that occur at the time cryopreservation is usually applied to embryos may have potential epigenetic risks. With advances in multi-omic single cell technologies, new ways to assess the (epi)genomic status during early embryo development have now become feasible. These novel strategies could provide a revolutionary opportunity to understand the actual impact of ART, but also may help future developments aiming at increase both their efficiency and safety. Here we outline insights in current knowledge and research on the impact of cryopreservation on embryos, the possible consequences at epigenetic level and how emerging new high-throughput technologies can be used for their assessment.